Improving the Quality of the Sales Function Model - Online Banking (Journal of Universal Excellence, 2026)
Research Question (RQ): How do banks improve sales or expand services? We want to find out if older people have a different view of online banking than younger people? Do the elderly see no future in online banking?Purpose: The purpose of the research is to investigate which method of sales/service in banking has the greatest impact on customers. To analyze how different generations are affected by the use of online banking.Method: Quantitative analysis is used in the research - we conducted an online survey using the 1KA application.Results: We found that online banking is the best option in banking sales. We found that even the elderly see the future in online banking. There was no significant difference between older and younger respondents in the analysis of the survey results.Organization: If the organization would consider the results and adapt to it, it would be a gain for the organization.Society: Online banking is an advantage for society, as we access our financial picture anywhere and anytime.Originality: The survey is original and the first of its kind for online banking.Limitations/Future Research: The survey was conducted on a small number of respondents in one region. Further research can be extended to more respondents in different regions and thus obtain a more representative sample.
Keywords: online banking; sales function; senior; junior; customers; survey; analysis; sales